Analisis Respon Hidrogeologi terhadap Stress Saat Terjadi Gempabumi (Studi Kasus Semburan Lumpur Setelah Gempa Tasikmalaya 2009 dan Pidie Jaya 2016) - J. Sinipar, Dimas Salomo; Erwin Wijaya, Andy; T. Listyani R.A. (ReTII, 2024)
Tectonic earthquakes often cause hydrogeological responses such as mudflows, but the mechanism by which stress during an earthquake triggers such responses is still unclear. The 2009 Tasikmalaya earthquake (M7.0), for example, triggered a mudflow in Pasirgede Village, Sukahening District, Tasikmalaya Regency, West Java. Another example is the 2016 Pidie Jaya, Aceh earthquake (M 6.5), which also triggered a mudflow in Meunasah Balek Village, Meureudu District, Pidie Jaya Regency, and in Benih Tamiang Village, Rantau District, Aceh Tamiang Regency. In this study, an investigation was conducted on volumetric strain, normal stress, and dynamic stress changes from tectonic earthquakes at the site location experiencing hydrogeological responses. The results show that the hydrogeological response is more caused by dynamic stress changes by seismic waves generated by the tectonic earthquake. This study is useful for understanding the hydrogeological response to stress that occurs during earthquakes, especially in relation to mitigating disaster events..